Identifikasi dan Diagnosis Kinerja Pompa Diafragma Wilden P200 Berbasis Computational Fluid Dynamics Menggunakan Solidworks - Tb. Ade Rahmatullah; Septano, Gurruh Dwi; Kristianti, Tika; Nasaruddin; Riyanto (Jurnal Teknik dan Science, 2026)
The Wilden P200 diaphragm pump is a critical component in fluid transfer systems; therefore, the stability of its performance has a direct impact on operational efficiency. In actual operating conditions, a significant reduction in the actual flow rate compared to the theoretical flow rate was identified, indicating performance degradation as well as potential non-compliance of the installation with the manufacturer’s recommended standards. This study was conducted using an inspection and fault diagnosis approach to systematically identify the root causes of the problem. The methodology included visual and functional inspection of components, observation of the piping installation, measurement of operating parameters, and performance analysis based on a comparison between actual and theoretical flow rates. The evaluation involved flow rate testing, volumetric efficiency assessment, and inspection of supporting components such as filters, check valves, and piping. The initial inspection results indicated the presence of flow restrictions, increased pressure losses, and a reduced capability of the pump to transfer fluid efficiently. To support the diagnostic process, Computational Fluid Dynamics (CFD) simulations were employed to visualize the pressure distribution, flow patterns, and potential pressure losses within the pump and piping system. The simulation results revealed high-pressure zones, flow constrictions, and significant pressure gradients, which were consistent with field observations, such as malfunctioning filters and sediment accumulation within the piping. Based on the combined results of field inspections and CFD analysis, it can be concluded that the performance degradation of the Wilden P200 pump is caused by a combination of component wear, filter malfunction, and the absence of routine inspection and maintenance procedures. These conditions lead to increased flow resistance and pressure losses, directly resulting in a reduction in the pump’s actual flow rate. The findings of this study are expected to serve as a basis for system improvements and the development of more effective maintenance strategies to prevent similar failures in future operations